Surface Modification Processes for Use in LEO, GEO and Planetary Environments - Jacob I. Kleiman (Mechanics and Advanced Technologies)
Abstract. ITL Inc. through its 30 years of activities in space exploration developed a number of unique processes for impairing new properties to space-bound materials that are exposed in LEO, GEO and planetary environments to space factors like atomic oxygen, ultraviolet radiation, charged energetic particles, etc.